Polypodium leucotomos targets multiple aspects of oral carcinogenesis and it is a potential antitumor phytotherapy against tongue cancer growth - Lacerda, Pammela A.; Oenning, Luan C.; Bellato, Guilherme Cuoghi; Lopes-Santos, Lucilene; Antunes, Natalícia de Jesus; Mariz, Bruno Augusto Linhares Almeida; Teixeira, Gabriela; Vasconcelos, Rafael; Simões, Gustavo Ferreira; de Souza, Ivani Aparecida; Pinto, Clóvis Antônio Lopes; Salo, Tuula; et al. (Frontiers in Pharmacology, 2023)
Introduction: Oral cancer refers to malignant tumors, of which 90% are squamous cell carcinomas (OSCCs). These malignancies exhibit rapid progression, poor prognosis, and often mutilating therapeutical approaches. The determination of a prophylactic and/or therapeutic antitumor role of the polyphenolic extract Polypodium leucotomos(PL) would be relevant in developing new tools for prevention and treatment. Methods: We aimed to determine the antitumor effect of PL by treating OSCC cell lines with PL metabolites and evaluating its action during OSCC progression in vivo. Results: PL treatment successfully impaired cell cycling and proliferation, migration, and invasion, enhanced apoptosis, and modulated macrophage polarization associated with the tumoral immune-inflammatory response of tongue cancer cell lines (TSCC). PL treatment significantly decreased the expression of MMP1 (p < 0.01) and MMP2 (p < 0.001), and increased the expression of TIMP1 (p < 0.001) and TIMP2 (p < 0.0001) in these cells. The mesenchymal-epithelial transition phenotype was promoted in cells treated with PL, through upregulation of E-CAD (p < 0.001) and reduction of N-CAD (p < 0.05). PL restrained OSCC progression in vivo by inhibiting tumor volume growth and decreasing the number of severe dysplasia lesions and squamous cell carcinomas. Ki-67 was significantly higher expressed in tongue tissues of animals not treated with PL(p < 0.05), and a notable reduction in Bcl2 (p < 0.05) and Pcna (p < 0.05) cell proliferation-associated genes was found in dysplastic lesions and TSCCs of PL-treated mice. Finally, N-cad(Cdh2), Vim, and Twist were significantly reduced in tongue tissues treated with PL. Conclusion: PL significantly decreased OSCC carcinogenic processes in vitro and inhibited tumor progression in vivo. PL also appears to contribute to the modulation of immune-inflammatory oral tumor-associated responses. Taken together, these results suggest that PL plays an important antitumor role in processes associated with oral carcinogenesis and may be a potential phytotherapeutic target for the prevention and/or adjuvant treatment of TSCCs